Structural equation modeling of collective decision-making's impact on group cohesion - S. Mirbagheri; A. Rafiei Atani; M. Parsanejad; R. Jafari (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: Cohesion is one of the most important factors in the sustainability of social relationships and organizational success. Evidence shows that many companies and organizations have failed or disappeared due to a lack of cohesion among their employees. For this reason, it is important to identify the factors that affect the convergence of individuals and strengthen the cohesion among them. The primary focus of this study revolves around the question of whether group cohesion can be enhanced through the utilization of a collective decision-making approach. Collective decision-making is about reaching a single decision by the group members. This research assesses the correlation between common rationality (as a basis for decision-making), collective decision-making, and cohesion.METHODS: To achieve the research purpose, a conceptual model is designed using the research background and interviews with experts, and then the structural equation method is used to achieve the research objectives, and Smart PLS 2.0 software is used to analyze the data. In this study, the concept of common rationality is examined as an exogenous factor, while cohesion is viewed as an endogenous factor, and collective decision-making is regarded as a mediating factor. To analyze the interplay among these factors, it is essential to assess the P-value, T-value, and regression coefficient, which are determined using structural equation modeling.FINDINGS:  The goodness of fit is employed to assess the overall model fit, which is obtained as 0.469, and this criterion indicates that the overall model fit of the research model is appropriate.The regression coefficient between the variables “common rationality → collective decision-making” is 0.668, and between the variables, “collective decision-making → cohesion” is 0.550, which shows a significant positive relationship between these variables. However, the regression coefficient between the variables “common rationality → cohesion” is 0.234, which indicates a weak relationship between these two variables. The findings suggest that common rationality has an impact on group cohesion by way of the intermediary factor of collective decision-making.CONCLUSION: Although common rationality is a significant asset for an organization and society, managers and governors who want to use it to increase cohesion must activate it through collective decision-making. By engaging diverse perspectives, enhancing communication, and developing collective skills, they can create environments where shared understanding and cohesive action thrive. This study can encourage managers and governors to use the collective decision-making method in their choices.